2013
DOI: 10.1371/journal.pone.0082360
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore Modeling and Virtual Screening for the Discovery of New type 4 cAMP Phosphodiesterase (PDE4) Inhibitors

Abstract: Type 4 cAMP phosphodiesterase (PDE4) inhibitors show a broad spectrum of anti-inflammatory effects in almost all kinds of inflamed cells, by an increase in cAMP levels which is a pivotal second messenger responsible for various biological processes. These inhibitors are now considered as the potential drugs for treatment of chronic inflammatory diseases. However, some recently marketed inhibitors e.g., roflumilast, have shown adverse effects such as nausea and emesis, thus restricting its use. In order to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The aromatic ring of the all known PDE inhibitors has shown crucial face to face -stacking interactions with Phe446. A study by Niu et al (Niu et al, 2013) also reported that two hydrogen bond acceptors, one hydrophobic ring and an aromatic group are critical Pharmacophoric features for PDE inhibitors (Niu et al, 2013). The compounds shown in Fig.…”
Section: Pharmacophoric Features In For Phosphodiesterases Inhibitorsmentioning
confidence: 96%
“…The aromatic ring of the all known PDE inhibitors has shown crucial face to face -stacking interactions with Phe446. A study by Niu et al (Niu et al, 2013) also reported that two hydrogen bond acceptors, one hydrophobic ring and an aromatic group are critical Pharmacophoric features for PDE inhibitors (Niu et al, 2013). The compounds shown in Fig.…”
Section: Pharmacophoric Features In For Phosphodiesterases Inhibitorsmentioning
confidence: 96%
“…The GH score ranges from 0 (indicates the null model) to 1 (indicates the ideal model). When the GH score exceeds 0.7, the model is very good to identify the active compounds [18,19]. The result was used to screen the pharmacophores of the phytoconstituents isolated from P. sagittatum (Fig.…”
Section: Protein Preparation and Validation Of The Pharmacophore Featmentioning
confidence: 99%
“…Pharmaceutical research in the field of chronic inflammatory disorders has made a step forward by developing new PDE4 inhibitors with a higher therapeutic index [88]. Apremilast, introduced to the clinic [35,89] and approved in the USA for the treatment of PsA [90], is one of these novel drugs, thus representing a promising tool for the medical treatment of other diseases mediated by the immune system.…”
Section: Apremilast In Immune-mediated Inflammatory Disordersmentioning
confidence: 99%